Regional anaesthesia, stimulation, and ultrasound techniques - Warman, Paul; Conn, David (Anaesthetist); Nicholls, Barry (Anaesthetist); Wilkinson, David J. ([Oxford] : Oxford University Press, 2014)
Regional anaesthesia is used across specialities within anaesthesia, and is a rapidly growing sub-speciality. This book covers both traditional and ultrasound guided techniques, concentrating on the differences between them.
Previously issued in print: 2014.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 23, 2016).
Keywords: Conduction anesthesia; Ultrasonic imaging